Pendaftaran Hak Pakai Berdasarkan Keberlakuan Undang-undang Nomor 4 Tahun 1996 Tentang Hak Tanggungan di Kota Malang - Moh. Ali; Dores, Dedi; Gunadi, Lie Eftani R.; Bagubau, Aprianus (Universitas Sains dan Teknologi Komputer, 2023)
This study examines the legal enforcement aspects of land rights registration management as a fundamental requirement for ensuring legal certainty and protection for rights holders. Under Law Number 4 of 1996 on Mortgage Rights, only registered land rights may legally serve as collateral for debt. The focus of this research is to analyze the implementation of use rights registration in Malang City and its impact on the enforcement of mortgage rights. The research employs both normative and empirical legal approaches, with data collected through literature review and interviews with relevant stakeholders. The findings reveal that a significant portion of the population has yet to register their use rights, rendering those rights ineligible as legal collateral. Contributing factors include limited public awareness, administrative obstacles, and insufficient outreach from responsible agencies. This study highlights the urgent need to enhance legal awareness and improve land administration services to support the effective and legitimate implementation of mortgage rights.